The effects of concept mapping on English as a foreign language (EFL) students' ability to summarize reading passages : - Phạm, Ngọc Quan (Trường Đại học Cần Thơ, 2017)
Nghiên cứu những ảnh hưởng của việc sử dụng sơ đồ khái niệm đến khả năng tóm tắt bài đọc của sinh viên chuyên ngành tiếng Anh.